How to lead smart people : leadership for professionals - Singh, Arun; Mister, Mike (London : Profile Books Ltd, 2019)
A guide for managers and leaders on how to motivate, communicate with, and lead highly skilled professionals and experts effectively.
Includes bibliographical references and index.
Keywords: Leadership; Management; Executives -- Psychology